Sport and Social Movements - Simon Darnell; John Horne; Sebastien C. O'Neill; Jean Harvey; Parissa Safai (Bloomsbury Academic, 2013)
This book examines the social movements challenging the world sport order, building on theories of alterglobalization.
English